Promovendo sustentabilidade na educação: um projeto de escola sustentável - Nunes, Marcela Eduarda de Oliveira (Brasil, 2025)
This project aims to implement a sustainable school in Manaus, focused on elementary education, that harmonizes architecture and the environment. The proposal adopts bioclimatic strategies to meet the specific climatic conditions of the Amazon region, such as high humidity, high temperatures and intense solar radiation. In addition to prioritizing the well-being of users, the project encourages environmental education and seeks to benefit the community, promoting sustainable practices and integration with nature.